Estrategia para la comercialización de maracuyá en la parroquia rural Patricia Pilar cantón Buena Fe provincia de Los Ríos zona 5 - Abad López, Lidia María (2016)
In Ecuador is a social problem since several decades and is the low income received by farmers in rural areas the same that disappoints its next generations creating over time a growing abandonment of productive land and bringing them to cities you overcrowded shantytowns creating these have in their geographical limitations. In the rural parish Patricia Pilar is has the second best climate in the world for the roduction of various fruits including passion fruit and necessary measures leading to this town owards agricultural development where you could think of repowering the nation creating mpanies generating value-added food and generate a better quality of life not only for locals but also create jobs that lead to economic development in the country.